Human Hair as a Possible Surrogate Marker of Retained Tissue Gadolinium: A Pilot Autopsy Study Correlating Gadolinium Concentrations in Hair With Brain and Other Tissues Among Decedents Who Received Gadolinium-Based Contrast Agents. Issue 10 (October 2020) - Hasegawa, Makoto; Duncan, Brianne R.; Marshall, Desiree A.; Gonzalez-Cuyar, Luis F.; Paulsen, Michael; Kobayashi, Masahiro; Simpson, Christopher; Maravilla, Kenneth R.
Abstract : Objectives: We used laser ablation inductively coupled plasma mass spectrometry to quantify gadolinium in hair samples from autopsy cases with gadolinium-based contrast agent (GBCA) exposure. Hair gadolinium data were correlated with gadolinium concentrations in brain, skin, and bone tissues from the same case to investigate a potential noninvasive method for gadolinium quantification and monitoring. Materials and Methods: Medical records from autopsy cases at our institution were screened for history of GBCA exposure. Cases with exposure to a single type of GBCA with the most recent injection occurring within 1 year were identified and included in the study. The concentration of gadolinium in hair samples was analyzed by laser ablation inductively coupled plasma mass spectrometry, and brain (globus pallidus, dentate nucleus, white matter), bone, and skin tissues were analyzed by bulk inductively coupled plasma mass spectrometry. The mean of the maximum value in the hair samples was used to generate a representative measurement of the hair gadolinium concentration for each case. A linear regression analysis between each tissue type and hair was conducted to assess for possible correlation. Results: Tissue and hair samples from 18 autopsies (16 cases with exposure to GBCA, 2 controls) were included in the study. Comparing the different tissues revealed good correlation between some tissue types. The best model fit occurred between white matter and hair ( R 2 = 0.83; P < 0.0001) followed by the comparison between dentate nucleus and hair ( R 2 = 0.72; P < 0.0001) and dentate nucleus and skin ( R 2 = 0.70; P < 0.0001). Conclusions: A significant correlation in this study between hair gadolinium concentrations and brain and skin gadolinium concentrations suggests that hair may serve as a safe and effective biomonitoring tissue for patients who receive GBCA injections.